Changes in the hydrometeorological conditions for sustainable water resources management in Sudan - Sahoo, Satiprasad; Govind, Ajit (CGIAR FOCUS Climate Security, 2022)
Agriculture is a pillar for the economy in Sudan, yet water resources may be decreasing as a result of climate change and agricultural operations, including flow management and irrigation techniques. Climate-resilient agriculture can help farmers build the capacity to adapt and effectively respond to long-term climate risk. It can also improve the irrigation system for agriculture production in rural development to increase food security. In this study, we analyzed the spatiotemporal trend of historical climatic data in Sudan at the sub-regional level. We also analyzed the spatiotemporal trends of historical hydrological parameters for sustainable and efficient use of water resources in the era of climate uncertainty. We developed a framework for terrestrial water storage and groundwater storage mapping for the variability of the dryness and wetness conditions using the Global Land Data Assimilation System (GLDAS) and Gravity Recovery and Climate Experiment (GRACE) data.